Validation and Verification of CFD Prediction of Fluid Flow of a Submerged Vertical Round Jet - Nurul Hasan; Ahmed Oliur Rahman; Md. Shah Alam (International Journal of Engineering Materials and Manufacture, 2018)
This paper presents a step by step verification and validation process of a vertical round submerged jet into a cylindrical bath. Taking advantage of the axi-symmetric domain, Navier-Stokes equation of primary is solved by finite volume method (FVM) using commercial computational fluid dynamics, CFD (Fluent) software. For verification and to minimise the computational error, step by step grid independence tests were performed. For validation, experimental data was produced using laser Doppler velocimetry (LDV). Among the turbulence model,  SST was found to predict the flow behaviour better than k-e-  realization or RSM models.